2007
DOI: 10.3727/000000007783465046
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Keratinocytes for Transplantation without the Need of Feeder Layer Cells

Abstract: Patients with large burn wounds have a limited amount of healthy donor skin. An alternative for the autologous skin graft is transplantation with autologous keratinocytes. Conventionally, the keratinocytes are cultured with mouse feeder layer cells in medium containing fetal calf serum (FCS) to obtain sufficient numbers of cells. These xenobiotic materials can be a potential risk for the patient. The aim of the present study was to investigate if keratinocytes could be expanded in culture without the need of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 44 publications
4
42
0
2
Order By: Relevance
“…Although Coolen et al (29) showed that keratinocytes can be cultured without a fibroblast feeder layer and fetal calf serum, the present results demonstrated that in the modified medium and onto a type I collagen scaffold (as a feeder layer), keratinocyte cell growth was greater than the condition without a feeder layer, and this is consistent with certain previous studies by Gingras et al (31) and Arpornmaeklong et al (32) in 2007. However, a long-term follow-up study is required to more precisely evaluate its fate following proper grafting.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although Coolen et al (29) showed that keratinocytes can be cultured without a fibroblast feeder layer and fetal calf serum, the present results demonstrated that in the modified medium and onto a type I collagen scaffold (as a feeder layer), keratinocyte cell growth was greater than the condition without a feeder layer, and this is consistent with certain previous studies by Gingras et al (31) and Arpornmaeklong et al (32) in 2007. However, a long-term follow-up study is required to more precisely evaluate its fate following proper grafting.…”
Section: Discussionsupporting
confidence: 82%
“…There are numerous studies that have focused on the development of nutritionally optimized, readily defined, reproducible media and culture conditions for keratinocyte cells (26)(27)(28)(29). The aims of the present study were not to establish a new medium, and therefore, the Rheinwald and Green (30) protocol was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Representative overlay histograms showed no difference in the positive staining for (a) the proliferation marker cytokeratin 14 (K14) and (c) the wound healing marker cytokeratin 6 (K6) between AK in different culture conditions. Anova all pair-wise comparison showed no statistically significant differences in the percentage of positive events of (b) K14 and (d) K6 between the different culture conditions (n = 3, p = 0.05) towards developing and testing defined medium conditions (Boyce and Ham 1983;Sun et al 2004;Coolen et al 2007;Mujaj et al 2010;De Corte et al 2011). In these experiments we did not test defined medium conditions beyond the use of EpiLife with EDGS.…”
Section: Discussionmentioning
confidence: 99%
“…The major issue with this study was the use of the irradiated mouse 3T3 feeder layer cells, which were regarded as a potential risk due to the possible transfer of disease, such as animal viruses or prions. In addition, the low number of CIN keratinocytes rescued was frequently associated with contaminant human fibroblasts, which rapidly overgrew the epithelial cells in culture (11)(12)(13). Additionally, the growth of the keratinocytes was constrained due to the limited space during the course of culture.…”
Section: Introductionmentioning
confidence: 99%